Peningkatan Kemampuan Komunikasi dan Prestasi Belajar Matematika Melalui Strategi Pembelajaran Two Stay Two Stray pada Siswa Kelas X SMK Muhammadiyah 1 Sukoharjo Tahun 2014/2015 - Hermawati, Windha, Rita P. Khotimah, S.Si., M.Sc (2015)
The purpose of this research is to improve communication skills and learning achievement in the application of learning strategies Two Stay Two Stray in class X TKR 2 SMK Muhammadiyah 1 Sukoharjo academic year 2014/2015. This research is a classroom action research. Data collection techniques, observation, testing, field notes, documentation, and interviews. The validity of the data using triangulation method. Data analysis techniques with interactive methods through a process of data reduction, exposure data, and drawing conclusions. The results showed that by applying TSTS learning strategies can improve communication skills and learning achievement in class X TKR 2 SMK Muhammadiyah 1 Sukoharjo academic year 2014/2015. The increase was shown by four indicators. (1) the ability of the students who answered questions from the teacher of initial conditions 16.13%, 48.39% first cycle and second cycle into 70.97%, (2) the ability of the students who put forward ideas or opinions of initial conditions 9.68% , 32.26% first cycle and second cycle into 67.74%, (3) the ability of student collaboration in a group of initial conditions 19.35%, 54.84% first cycle and second cycle into 83.87%. (4) the ability of students to present the results of the discussion of the initial condition of 12.90%, 38.71% first cycle and second cycle into 70.97%, student achievement to reach the KKM (≥70) from baseline 22.58 %, 48.39% first cycle and second cycle into 80.64%.